Pertanggungjawaban Perusahaan PT. Garuda Indonesia yang Diduga Melakukan Praktik Diskriminasi Terkait Pemilihan Mitra Penjualan Tiket Umrah - Amelia Ridha Rahman; Rani Apriani (Universitas Islam Balitar, Blitar, 2023)
This research is to determine the form of corporate responsibility PT. Garuda Indonesia, which is suspected of discriminating in the selection of partners for selling Umrah tickets, uses normative legal research methods, by examining literature that focuses on Law no. 5 of 1999. The results of this study are the accountability carried out by PT. Garuda Indonesia in resolving the case, by paying a fine or administrative sanction determined by the Indonesian Competition Commission (ICC), namely paying a fine of IDR 1,000,000,000.00. However, if the fine is late in payment, PT. Garuda Indonesia may be subject to a late fine of 2% per month of the specified fine, in accordance with Government Regulation Number 58 of 2020 concerning the Management of Non-Tax State Revenue.